A bibliographic review of the history of Dexiinae (Diptera, Tachinidae) taxonomy in the Neotropical Region with bibliographic notes on Dominik Bilimek and Fritz Plaumann - de Santis, Marcelo Domingos (Arquivos de Zoologia, 2022)
The knowledge of Dexiinae and Tachinidae diversity in the Neotropical Region, in contrast to other regions, e.g., the Palaearctic Region, is in a poor condition. The history of these taxa has gradually increased since the 18th Century from the works of European and North American authors such as Johan C. Fabricius, Christian R.W. Wiedemann, Jean B. Robineau-Desvoidy, Pierre J.-M. Macquart, Jacques M.F. Bigot, Francis Walker, Victor von Röeder, Ermanno Giglio-Tos, Friedrich M. Brauer and Julius E. Bergenstamm, Frederik M. van der Wulp, Charles H. Curran, John M. Aldrich, Charles H.T. Townsend, Henry J. Reinhard and William R. Thompson. It was only in the first half of the 20th Century that scientists born or established in South America began to enter tachinidology. Dipterists like Jean Brèthes and Everardo E. Blanchard from Argentina, Rául E. Cortés Peña from Chile and José H. Guimarães from Brazil, are the most memorable names for, not only to Neotropical Dexiinae, but, indeed for the whole family. Herein, a brief chronological review of tachinidology, with emphasis on Dexiinae and based on a literature review, is given. The history is divided into four periods: the pre-Linnaean period of the 16th and 17th Centuries, the 18th Century, the 19th Century and the first half of the 20th Century. After the first half of 20th Century, the emphasis is focused on European and North American dipterists with an overview of their contributions on Dexiinae taxonomy. Later, with presence of the South American dipterists, the emphasis is directed to them. Then a few notes are given on the Czech Dominik Bilimek, a poorly known collector from the 19th Century and Fritz Plaumann, a well-known German immigrant who collected in Brazil during the earlier 20th Century. Finally, some notes and perspectives about the 21st Century dexiinidology from the Neotropics is briefly discussed.